Kualitas Pelayanan Digital di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Kepulauan Sangihe (JURNAL ADMINISTRASI PUBLIK, 2024)
ABSTRACTThis research aims to determine the quality of digital services in the population and civil registration services of Sangihe Islands Regency. The research carried out was descriptive research using a qualitative method. Information collection uses observation, interview and documentation techniques. In this research, data analysis uses data reduction, data presentation, and drawing conclusions. The results of the research show a quality of digital services using five indicators, namely: 1. "reliability" which means that a public administrator's knowledge of service delivery is good. This can be seen from the results of observations and interviews where there are supporting elements such as service standards and SOPs that have been implemented. clear. 2. "Responsiveness" in the implementation of this service is considered good because the informants gave a positive response in which the service implementers provided the service swiftly and deftly according to their competence. 3. "Guarantee" is not done well. This can be seen from the perspective that the service implementation is good, but what makes it less good is the technical elements such as server problems caused by the network, etc. 4. "Empathy" relating to individual attention from employees is very good and satisfactory, this can be seen from the positive responses of informants. 5. "Tangible" with infrastructure facilities is concluded to be not good, this can be seen from the lack of facilities to support this service.Keywords: Quality, Public Services, Digital